Compliance with a massive transfusion protocol (MTP) impacts patient outcome. Issue 1 (January 2015) - Bawazeer, M.; Ahmed, N.; Izadi, H.; McFarlan, A.; Nathens, A.; Pavenski, K.
Abstract: Background: About 5% of civilian trauma requires massive transfusion. Protocolized resuscitation with blood products to achieve high plasma:RBC ratio has been advocated to improve survival. Our objectives were to measure compliance to our institutional MTP, to identify quality assurance activities that could improve protocol compliance and to determine if protocol compliance was related to patient outcome. Methods: The investigators determined 13 compliance criteria based upon our institutional protocol. We measured compliance in 72 consecutive MTP activations between January 2010 and September 2011 at a Level I trauma centre. Data elements were retrospectively retrieved from blood bank, trauma registry and clinical records. Patients were stratified into three groups based on compliance level, and mortality differences were compared. Results: Average compliance for the cohort ( n = 72) was 66%. The most common cause of non-compliance was failure to send a complete haemorrhage panel from the trauma bay (96%). Failure to monitoring blood work every 30 min occurred in 89% of cases. Delay in activation and deactivation occurred in 50% and 50% respectively. Non-compliance to protocol-based administration of blood products happened in 47%. The cohort was stratified into three groups based on compliance, A: <60%, B: 60–80% and C: >80% (low, moderate and high compliance groups). There was no statistical significance with regard to median age, median ISS, ED SBP, ED GCS and AIS of the head/spine, chest and abdomen. The mortality rates in each group were 62%, 50% and 10% in the low, moderate and high compliance groups respectively. Mortality differences were compared using adjusted logistic regression. The OR for mortality between Groups A and B = 1.1 [95% CI 0.258–4.687 ( P = 0.899)] while the OR for mortality between Groups C and B = 0.02 [95% CI <0.001–0.855 ( P = 0.041)]. Conclusions: Measures should be directed towards provider and system factors to improve compliance. In this study, there was an association between survival and higher level of compliance.